The effect of religiosity and religious festivals on positional concerns: An experimental investigation of Ramadan - Alpaslan Akay; Gökhan Karabulut; Peter Martinsson (Institute for the Study of Labor (IZA), 2011)
This paper examines the effect of religion on positional concerns using survey experiments. We focus on two of the dimensions of religion - degree of religiosity and religious festivals. By conducting the experiments during both the most important day of Ramadan (the Night of Power) and a day outside Ramadan, we find that Ramadan overall has a small and negative impact on positional concerns. Detailed analyses based on the sorting of individuals' degree of religiosity reveal that the decrease in the degree of positional concerns during Ramadan is mainly explained by a decrease in positionality among individuals with a low degree of religiosity. We also discuss the broader welfare implications of our findings.
urn:nbn:de:101:1-201201103035
Keywords: C90; D63; 330; positional concerns; religion; Ramadan; Islam; Religion; Islam; Externer Effekt; Sozialer Status